PENGARUH LOKASI, HARGA, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN BERBELANJA DI MATAHARI DEPARTMENT STORE JAVA MALL SEMARANG - Dris Dumasi Hamuda; Saryadi Saryadi (Universitas Diponegoro, 2018)
This research is motivated by the phenomenon of the rise of a variety of trade center such as department store in Indonesia marks a change in consumer shopping behavior from tradisional market to modern market. Matahari Department Store is one of the largest department store fashion and always visited by most of people in Indonesia. The involvement of location, price, and service quality are very important in shopping decision. The problems in this research was the decline in the percentage of achievement target the sale of the Matahari Department Store Java Mall Semarang. While the purpose of this research is to find how influence of location, price , and service quality to the shopping decision whether partially and simultaneously.This type of research is the explanatory research. Based on Cooper & Emory formula, total sample used in this study is 100 respondents were aged between 17 years up to 60 years and has bought in the Matahari Department Stores Java Mall Semarang in 2016.The result of this study show that the influence exerted by variable location to the shopping decision is 54,6%, variable the price to the shopping decision is 64%, and variable service quality to the shopping decision is 71,4%. In addition, the influence exerted by variable location, price, and service quality to the shopping decision of 74%. From the research found that the biggest influences that affect the shopping decision variable at Matahari Department Store Java Mall Semarang is the variable service quality (X3). From the discussion, we can conclude that location, price, and service quality positively influence to the shopping decision at Matahari Department Store Java Mall Semarang. But there were a number of things for those unsatisfactory in terms of location, the price of, and service quality. For that reason, management of Matahari Department Store Java Mall is expected to be more increase by a factor of strategic’s location, price set ,and service quality for the increasing of shopping decision.